THE VALUE OF RED CELL DISTRIBUTION WIDTH (RDW) AND NEUTROPHIL-LYMPHOCYTE RATIO (NLR) ON THE SEVERITY OF CHILD PNEUMONIA : A CORRELATION STUDY - Sasmito, Nanang Bagus; Roni Setiawan; Intan Puspita Rahayu (Universitas Kadiri, 2025)
Pneumonia is the leading cause of childhood morbidity and mortality in Indonesia today. Challenges in determining the severity of pneumonia quickly and accurately contribute to the increase in cases, so the identification of hematologic biomarkers predictive of clinical worsening is important. The aim of this study was to assess the relationship of RDW and NLR to the severity of pneumonia in pediatric patients at Jombang Regional Hospital. This research design uses Analytical Observational with Retrospective Cohort Study approach. The total population of all patients was 100 with a research sample of 50 patients. This study used purposive consecutive sampling technique. The measurement tool for pneumonia severity used the PRESS (Pediatric Respiratory Severity Score) indicator in the form of a research sheet and data analysis using the Spearman Rank Test. The results of this study showed that most samples were in the age group of 1 month - 1 year (52.00%) with the highest gender of male (62.0%). The average RDW and NLR values were 15.050% and 2.91, respectively, with the most pneumonia severity category in the moderate category (66%). Based on the results of statistical tests using Spearman Rank, the significance values of RDW (ρ = 0.000 and r = 0.501) and NLR (ρ = 0.000 and r = 0.622) can be concluded that there is a significant relationship between RDW and NLR on the severity of pneumonia in pediatric patients in the Srikandi Ward of Jombang Hospital. An increase in RDW is a reaction to the release of cytokines as a response to inflammatory stress, while an increase in NLR is a reaction to an increase in neutrophils and a decrease in lymphocytes which indicates an inflammatory process. Thus, RDW and NLR values can be used as cheap, simple, fast and accurate hematologic biomarkers to assess the severity of pneumonia in children.